F54. Food intake can significantly influence tilt table test results in patients with postural orthostatic tachycardia syndrome. (May 2018) - Crnošija, Luka; Ruška, Berislav; Skorić, Magdalena Krbot; Adamec, Ivan; Habek, Mario
Abstract : Introduction: Postural orthostatic tachycardia syndrome (POTS) is a form of orthostatic intolerance characterized by excessive heart rate (HR) increase when in an upright posture, accompanied by characteristic symptoms such as lightheadedness, weakness, nausea, fatigue etc. Following criteria must be met when diagnosing POTS: (1) sustained heart rate (HR) increment of ⩾ 30 bpm within 10 min of standing or head-up tilt in the absence of orthostatic hypotension; (2) a history of characteristic symptoms that are relieved by recumbency. Considering the known and significant impact a meal intake can have on autonomic nervous system activity, we aimed to investigate the effect of food intake on HR in patients with POTS. Methods: Forty-one subjects who fulfilled POTS criteria on an initial tilt table test performed the following protocol within the next 28 days: (1) 10-min supine phase, (2) 10-min 70° tilted phase, (3) ingestion of 400 ml (616 kcal) of liquid meal replacement, (4) 45-min supine phase and (5) 10-min 70° tilted phase. All the participants were fasting at least 3 h prior to the testing. Subjects were divided into three groups: (A) difference ( Δ ) in HR (standing vs. supine) ⩾ 30 bpm before the meal ( N = 13); (B) Δ HR < 30 bpm before the meal, but ⩾ 30 bpm after the meal ( N = 12); (C) Δ HR < 30 bpm before and after the meal ( N = 16). Group D consisted of 10 healthy subjects. Results: There were no significant differences in age and sex between the groups ( p = 0.203 and p = 0.112). There were no differences in the supine HR and supine or tilted systolic or diastolic blood pressure before or after the meal between groups (all p > 0.05). Before the meal, Δ HR was significantly higher in group A compared to all other groups, and in group B compared to group D ( p < 0.00000001). After the meal, Δ HR was significantly higher in group A compared to all other groups, and in group B compared to groups C and D ( p < 0.0000000001). We than pooled patients from group A and B into a POTS group, and patients from group C and D into a non-POTS group, and performed ROC analysis for the tilt-up test before and after the meal. Before the meal, a cut-off value of 30 bpm HR increase upon tilt-up had the sensitivity of 52.0% and specificity of 96.2%, while a cut-off value of 25 bpm increase had sensitivity of 92.0% and specificity of 80.8%. After the meal, a cut-off value of 30 bpm increase of HR had the sensitivity 100.0% and specificity of 92.3%. Conclusion: Food intake can significantly alter the results of the tilt table test and should be taken into account when diagnosing POTS. Performing the tilt-up test after a controlled food intake may increase the test quality (sensitivity and specificity), but this hypothesis should be tested in a larger sample of patients and healthy subjects.